If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -1(5x + -3) = 26 Reorder the terms: 3x + -1(-3 + 5x) = 26 3x + (-3 * -1 + 5x * -1) = 26 3x + (3 + -5x) = 26 Reorder the terms: 3 + 3x + -5x = 26 Combine like terms: 3x + -5x = -2x 3 + -2x = 26 Solving 3 + -2x = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2x = 26 + -3 Combine like terms: 3 + -3 = 0 0 + -2x = 26 + -3 -2x = 26 + -3 Combine like terms: 26 + -3 = 23 -2x = 23 Divide each side by '-2'. x = -11.5 Simplifying x = -11.5
| ln(x-2)-ln(x+3)=ln(x-1)-ln(x+7) | | -7(a-8)=7 | | 7s^2-19st+10t^2=0 | | 12x^5-11x^7+15x^8=0 | | 9x-7y=8 | | 6q=24q+6 | | x+(x+6)=4 | | 41-q=3q-15 | | 5-2p=6*q+1 | | 28+y=90 | | f(-11.9)=[-11.9+.5]-3 | | 25+2t=5t+10 | | -15=x-35 | | -16t^2+32t+768=528 | | 8+2(x-5)=5x-11 | | 6x^4+22x^3+11x^2-38x-40=0 | | 0=-16t^2+32t+768 | | 0=-16t^2+48t+768 | | 3x^2=-2x-9 | | 5z-3=2z-6 | | -6g^2-8g+6=0 | | 36x^2-60=-25 | | 0=-16t^2+6400 | | -2r^2+8r-8=0 | | 4q+1=3q-6 | | 0=-16t^2+3600 | | -7s^2+7s=0 | | y-t+y+t-2y= | | j^2+9j+8=0 | | 3k^2-5k+2=0 | | 90*3*-5*-2=3*-5 | | 6(2t-1)+5=12-t |